An analytical model for sparse and dense vehicular ad hoc networks - Najafzadeh, Sara (Springer, 2011)
Vehicular Ad hoc Network (VANET), a subclass of mobile ad hoc networks (MANETs), is a promising approach for the intelligent transportation system (ITS). The design of routing protocols in VANETs is important and necessary issue for support the smart ITS. The key difference of VANET and MANET is the special mobility pattern and rapidly changeable topology. Besides, the temporary network fragmentation problem and the broadcast storm problem are further considered for designing protocols in VANETs. The temporary network fragmentation problem which happens in sparse network caused by rapidly changeable topology influence on the performance of data transmissions. The broadcast storm problem in dense network seriously affects the successful rate of message delivery in VANETs. This paper presents an analytical model for sparse and dense Vehicular Ad hoc Networks.